2017
DOI: 10.1097/dcr.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Quality of Life of Patients With Permanent End Ileostomy: Results of a Nationwide Cross-Sectional Survey

Abstract: Quality of life was markedly impaired in patients with permanent end ileostomy as compared with the general population. The main reasons were stoma-associated morbidity and nutritional deficiency syndromes. These findings highlight the importance of prevention, screening, and adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 30 publications
2
59
0
4
Order By: Relevance
“…Our study reported a rate of stoma formation of 11.5% when surgery is performed electively, compared to 22% in the emergency setting. The presence of a stoma can significantly affect patients’ quality of life [23, 24] and is also associated with a risk of complications and re-interventions [25]. A stoma rate up to 35% has been described for complicated CD [26] and a penetrating phenotype of CD may explain a more common use of stomas in selected patients, because of abscesses and intra-abdominal contamination, or due to complex fistulae requiring more than one intestinal resection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reported a rate of stoma formation of 11.5% when surgery is performed electively, compared to 22% in the emergency setting. The presence of a stoma can significantly affect patients’ quality of life [23, 24] and is also associated with a risk of complications and re-interventions [25]. A stoma rate up to 35% has been described for complicated CD [26] and a penetrating phenotype of CD may explain a more common use of stomas in selected patients, because of abscesses and intra-abdominal contamination, or due to complex fistulae requiring more than one intestinal resection.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Mazloomymahmoodabad et al, showed Education Based on Precede-Proceed quality of life score in experimental as compared to control groups following an intervention [38]. Because oral health is an aspect of an individual’s quality of life [39, 40], it was expected that educational interventions would increase the mean total score of quality of life and the average score of different dimensions of quality of life in the elderly, according to a study conducted on the life quality of the elderly [41]. In the present study, the significant difference between the two groups following the educational intervention is a good indicator of the effect of educational intervention on improving the oral health related quality of life of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Prolapse is known to correlate with poor quality of life outcomes in patients with a long-term stoma [15], with patients demonstrating reduction in both physical and mental component scores of the generalized quality of life questionnaire SF-36 [16], as well as a significantly lower scores when assessed with Gastrointestinal Quality of Life Index (GIQLI) [17]. We note that from this select series that prolapse in this group of children happens relatively early after initial stoma formation and this may prompt the attending surgeon to consider surgery addressing the issue early in the patient journey.…”
Section: Discussionmentioning
confidence: 99%